Esterification of highly acidified oil using waste cooking oil and ionic liquid supported by divinyl benzene as catalyst - Nor Shahroon, Hameed Sultan (2015)
The depletion of natural resources around the world led the researcher looking forward for alternatives renewable sources. Biodiesel has been chosen as a good alternative to replace the petroleum. Many researchers used virgin oil as the raw material to produce biodiesel. However, virgin oil is quite expensive and increased the competition between food and fuels. Therefore, waste cooking oil has been chosen as the alternative feedstock used in this research compared to edible oil. On the other hand, acidified oil such as waste cooking oil and animal fats was found to gives a good conversion of triglycerides via the two step esterification- transesterification reaction. Esterification process is needed in the pretreatment of acidified oil to reduce the FFA content in the feedstock itself before it could be proceed with transesterification. The objective of this study is to synthesize and characterize the triethylammonium hydrogen sulphate ionic liquid and supported triethylammonium hydrogen sulphate ionic liquid and to conduct the catalytic esterification reaction using both type of catalyst. The catalyst was characterized using NMR, FTIR, SEM and BET. The NMR spectrum are as 1HNMR, (500MHz, DMSO) (ppm): ∂ 1.19 (triplet, 9h) ∂ 3.09 (multiplet, 6H) ∂ 6.95 (singlet, 1H) ∂ 9.01 (singlet, 1H). The IR spectrum of ionic liquid are sulphonic acid at 1061 and 1149 cm-1, including C-C (1233 cm-1), Ar-H (2506 cm-1) and OH (3037 cm-1). The IR spectrum for supported ionic liquid are 1101 and 990 cm-1 for sulphonic group, C-C (1168 cm-1), Ar-H (2924 cm-1) and OH (3445 cm-1). The supported ionic liquid has surface area of 22.34 m2 /g and the pore volume is 0.0327cm3/g. The pore size of supported ionic liquid is 2.6 nm. The esterification of highly acidified oil is conducted at temperature of 600C, 2.5 wt % of catalyst and the molar ratio of methanol to waste cooking oil of 18:1. As a conclusion, both catalysts are not able to reduce free fatty acid and have zero conversion. This is due to unsuitable ratio of methanol to oil and temperature of the reaction.